Extraction, purification, structural characteristics and biological properties of the polysaccharides from Codonopsis pilosula: A review. (1st June 2021) - Luan, Fei; Ji, Yafei; Peng, Lixia; Liu, Qi; Cao, Haijuan; Yang, Yan; He, Xirui; Zeng, Nan
Highlights: Codonopsis pilosula polysaccharides (CPPs) are well-known nutraceutical food. Preparation methods and structural characteristics of CPPs are summarized. Multiple biofunction activities and action mechanisms of CPPs are highlighted. CPPs exhibit broad application prospects in pharmaceuticals and functional foods. Further investigations are required to accelerate a better understanding of CPPs. Abstract: Codonopsis pilosula (Franch.) Nannf., as a well-known homology plant of medicine and food, has the function of replenishing the Qi, strengthening the spleen and tonifying the lung, nourishing the blood and engendering the liquid in traditional Chinese medicine. Accumulating evidence has demonstrated that the C. pilosula polysaccharides (CPPs) are one of the major and representative pharmacologically active macromolecules and present multiple biological activities both in vitro and in vivo methods, such as immunomodulatory, antitumor, antioxidant, neuroprotective, antiviral, anti-inflammatory, anti-fatigue, hypoglycemic, anti-hypoxia, renoprotective, gastroprotective, hepatoprotective, and prebiotic. The purpose of the present review is to provide comprehensively and systematically reorganized information in the extraction and purification, structure characterization, biological activities and the underlying mechanisms of action as well as toxicities of CPPs to support their therapeutic potentials and sanitarian functions. New valuable insights for the future researches regarding CPPs were also proposed in the fields of therapeutic agents and functional foods.